2013
DOI: 10.1120/jacmp.v14i2.4046
|View full text |Cite
|
Sign up to set email alerts
|

Migration of implanted markers for image‐guided lung tumor stereotactic ablative radiotherapy

Abstract: The purpose of this study was to quantify postimplantation migration of percutaneously implanted cylindrical gold seeds (“seeds”) and platinum endovascular embolization coils (“coils”) for tumor tracking in pulmonary stereotactic ablative radiotherapy (SABR). We retrospectively analyzed the migration of markers in 32 consecutive patients with computed tomography scans postimplantation and at simulation. We implanted 147 markers (59 seeds, 88 coils) in or around 34 pulmonary tumors over 32 procedures, with one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…19 It also concluded that despite the difference in retention rates between FM, once retained, the migration distance was limited and similar among the various FMs. 19 At our institution, we utilized SBRT with Cyberknife in 235 patients for the management of nonoperable lung cancer. We made use of various methods of deployment of FM including bronchoscopy with fluoroscopy guidance alone and with electromagnetic navigation bronchoscopy (ENB) direction.…”
Section: Fiducial Markersmentioning
confidence: 97%
See 4 more Smart Citations
“…19 It also concluded that despite the difference in retention rates between FM, once retained, the migration distance was limited and similar among the various FMs. 19 At our institution, we utilized SBRT with Cyberknife in 235 patients for the management of nonoperable lung cancer. We made use of various methods of deployment of FM including bronchoscopy with fluoroscopy guidance alone and with electromagnetic navigation bronchoscopy (ENB) direction.…”
Section: Fiducial Markersmentioning
confidence: 97%
“…19 This is crucial in the setting of SBRT as it confirms the reliability of fiducials as markers for tumor tracking and treatment planning. 19 It also concluded that despite the difference in retention rates between FM, once retained, the migration distance was limited and similar among the various FMs. 19 At our institution, we utilized SBRT with Cyberknife in 235 patients for the management of nonoperable lung cancer.…”
Section: Fiducial Markersmentioning
confidence: 98%
See 3 more Smart Citations